Viability studies of Pseudomonas fluorescens, Pf 1 in liquid formulation, its effect on plant growth and on root knot nematode, Meloidogyne incognita - MEENA, K SANKARI; JONATHAN, E I; DEVRAJAN, K (The Indian Journal of Agricultural Sciences, 2014)
Viability of Pseudomonas fluorescens, Pf 1 in liquid formulation amended with different chemicals was studied for a period of one year. Among the amendments tested, NB with 10 mM glycerol showed maximum viability of Pf 1 cells (360 days). Similarly, in stickers, NB with starch (2%) showed the maximum viability of Pf 1 cells (240 days). Plant growth promotion studies carried out in tomato cv Co3 under roll towel and pot culture method revealed that fifth day old culture of Pf 1 showed enhanced plant growth when compared with other subsequent day old cultures. Under in vitro studies against Meloidogyne incognita, the same fifth day old culture at its 25 per cent concentration recorded the least egg hatching and maximum juvenile mortality. However, the efficiency of different days old cultures remained effective over control for a period of one year when stored as liquid formulation along with chemical amendments.